Development of Flipbook as Learning Media to Improve Eighth Grade Students’ Vocabulary Mastery - I Kadek Pasek Aditya; Utami, I G A Lokita Purnamika; Mahayanti, Ni Wayan Surya (EDULIA: English Education, Linguistic and Art Journal, 2026)
This research aimed to develop an interactive flipbook as a learning medium to help eighth grade students master vocabulary at SMPN 3 Banjar. The study used the Design and Development (DnD) method with the Design, Development, and Evaluation (DDE) model. The research involved 30 students of class VIII 1. The design stage was based on students’ learning needs questionnaires and teacher interviews. The flipbook was developed using Canva, Heyzine, and Quizizz. The evaluation stage included quality judgment and practicality testing. The quality judgment conducted by research supervisors showed an average score of 78, which was categorized as very good based on the Ideal Mean (Mi) and Ideal Standard Deviation (SDi) analysis. In addition, the practicality test involving 30 students obtained an average score of 58.37, indicating that the learning media was categorized as very practical.   Keywords: Design, Development, Evaluation, Flipbook, Vocabulary.